2007
DOI: 10.1097/phm.0b013e31802ede64
|View full text |Cite
|
Sign up to set email alerts
|

Functional vs. Strength Training in Disabled Elderly Outpatients

Abstract: These data suggest that an intensive FT intervention results in strength improvements of comparable magnitude as those attained from ST and that FT also confers greater improvements in dynamic balance control and coordination while performing daily life tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 39 publications
1
68
0
6
Order By: Relevance
“…Cress et al used a twogroup nonrandomization design [9]. Six trials applied a two-group randomized controlled trial design: three trials compared functional training to an attention placebo control group [17,31,18]; one trial compared functional training to a control group who engaged in flexibility exercises [1]; one trial compared two programs that differed in functional training dosage, home exercise versus combined home and group exercise [21]; and one trial compared functional training to strength training [28]. Among three trials that applied a three-group randomized controlled trial design, in addition to a functional training group: two trials included a strength training group [35,11]; two trials included a control group [11,8]; one trial included a strength plus functional training group [35]; and one trial included a strength plus balance training group [8].…”
Section: Cohort Characteristicsmentioning
confidence: 99%
“…Cress et al used a twogroup nonrandomization design [9]. Six trials applied a two-group randomized controlled trial design: three trials compared functional training to an attention placebo control group [17,31,18]; one trial compared functional training to a control group who engaged in flexibility exercises [1]; one trial compared two programs that differed in functional training dosage, home exercise versus combined home and group exercise [21]; and one trial compared functional training to strength training [28]. Among three trials that applied a three-group randomized controlled trial design, in addition to a functional training group: two trials included a strength training group [35,11]; two trials included a control group [11,8]; one trial included a strength plus functional training group [35]; and one trial included a strength plus balance training group [8].…”
Section: Cohort Characteristicsmentioning
confidence: 99%
“…This addition may be especially important for shorter subjects and those with greater BMI or BW levels such as group 1 subjects in this study. In a randomized, blinded, prospective clinical trial evaluating 15 subjects (aged 62-85) who had at least one lower-limb impairment, Krebs et al reported that subjects (n = 9) who participated in a functional training program demonstrated a more effective anterior-to-vertical momentum transfer strategy by displaying greater internal knee extensor torque during chair-rise performance compared with subjects (n = 6) who trained using conventional strength-training exercises [35]. Groups 1 and 2 that did not perform as well in our study had a greater percentage of women, had a greater BMI or BW, were shorter, and had weaker quadriceps femoris muscle group strength at both the involved and noninvolved lower limb.…”
Section: Figurementioning
confidence: 99%
“…Studies comparing different neuromuscular training protocols have shown that the benefits of exercises depend on tasks performed during training, and greater gains in functional capacity require specific movements for daily tasks, so as to prevent the onset of physical disabilities. [5][6][7] In this context, functional training (FT) arises with the basic premise of training the psychobiological system in an integral way. This new method is based on the application of a systematized program of integrated, multi-articular and multi-planar exercises aimed at improving movement ability, the strength of the CORE region, and neuromuscular efficiency for the specific needs of each individual.…”
Section: Introductionmentioning
confidence: 99%